Gonadotropin supplementation improved in vitro developmental capacity of Egyptian goat oocytes by modulating mitochondrial distribution and utilization - AbdElkhalek, A. S.; Soliman, M. G.; El Naga, N. A. A.; El Bahrawy, K. A.; Kamel, A. M.; Shedeed, H. A.; Ghanem, N. (Journal of the Indonesian Tropical Animal Agriculture, 2024)
Goat production in Mediterranean countries is economically and socially significant. The study investigated the impact of hCG supplementation on the in vitro maturation, fertilization, and mitochondrial activity of goat oocytes. In total, 2356 good cumulus-oocyte complexes (COCs) were recovered from 476 freshly collected goat ovaries. Selected oocytes were incubated in IVM medium and supplemented with hCG at varying concentrations depending on the experimental group for 24 hours at 38.5 ° C, 5% CO2 and 95% humidity. The first group (G1) was allocated as a control group, while the G2 and G3 groups were supplemented with 10 and 20 IU/mL hCG, respectively. The maturation rate was calculated using Hoechst 33342 staining in addition to cumulus expansion and the first polar body extrusion rates. The fertilization rate was evaluated. Moreover, mitochondrial activity was assessed using Mito-Tracker fluorescent staining. The results indicated a higher rate (P≤0.05) of nuclear maturation in G3 (82.5%) than in G2 (65.9%) and the control group (64.8%). Furthermore, fertilization rate was significantly improved in G3 (18.7%) compared to G2 (10.6%) and the control group (9.5%). Notably, the percentage of diffuse patterns of mitochondrial distribution increased in G3 (73.3%) compared to G2 (13.3%) and the control group (6.7%). In the same trend, the fluorescent mitochondrial intensity was higher in G3 (95%) and G2 (89.2%) compared to the control group (79.9%). In conclusion, supplementing the IVM medium with 20 IU/mL of hCG improved goat oocytes' maturation and fertilization rates by modulating cytoplasmic distribution and promoting the utilization of oocyte mitochondria.